Impact of Digital Transformation on Reducing Money Laundering - Kadhim H. Hamad (PT SOLUSI EDUKASI BERDIKARI, 2026)
Digital transformation has become an important strategy for improving banking efficiency, transparency, and risk management. Meanwhile, money laundering remains a major challenge that threatens financial system stability. This study examines the impact of digital transformation on reducing money laundering in government and private banks in Babylon Governorate, Iraq. A quantitative descriptive-analytical approach was applied using questionnaire data collected from 100 bank employees. Data were analyzed using SPSS through descriptive analysis, one-sample t-test, and Pearson correlation analysis. The results indicate that digital transformation implementation has reached a significant level and contributes positively to reducing money laundering activities. The findings highlight the importance of digital infrastructure, employee capabilities, and technology-based monitoring systems in strengthening anti-money laundering practices in banking institutions.